(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Significant studies were undertaken on the use and impact on tensile along with compressive strength of the recycled concrete aggregate (RAC). However, the combined result of recycled aggregate and fly ash (FA) on tensile and compressive strength of concrete has not been modelled properly. To contribute to this area, research was carried out in combination with Fly ash and substitution per cent of natural coarse aggregates by recycled aggregates along with different water-cement ratios. This study determines whether the numerical analysis can be performed on the experimental values of strengths or not. By the checking normality, one-way analysis of variance (ANOVA) is used as working method. The predictive model for reliability is trained and tested upon the available experimental data sets. Thus, the research work briefs about the numerical analysis by statistical methods and the corresponding result analysis. The linear relationship between the Concrete mix % and with & without fly ash provides the reliability of the model. 90 days Compressive and Tensile strength at 0.38 w/c for 20% RAC & 10% FA provides the best choice among all and can be further optimized on its various combinations.